The EU's neighbouring economies: emerging from the global crisis (Luxembourg, 2010)
"The EU's neighbouring economies face new challenges in the aftermath of the global crisis. The EU's eastern neighbours reached a deep trough in 2009 while growth in the EU's southern neighbours was halved. Although this makes the return road towards the growth that was achieved before the crisis less steep for the latter region, it may not be easier. Challenges prominent before the crisis, such as surging commodity prices, may reappear on the back of the resurgence of global economic growth. This review analyses the economic, monetary and financial developments as well as the challenges: high fiscal debt stocks, sizeable government sectors, relatively weak private sectors, high unemployment rates and shallow financial sectors threaten to hamper the rise of economic activity and damage welfare levels. The strikingly different developments of the relative income levels of the southern and eastern regions during the last decades are also illustrated; while the southern neighbours had already reached a higher welfare level than the eastern neighbours at the beginning of the century, their economic growth has been far slower during the last decade. In view of their rapid growth performance before the global crisis, the eastern economies seem well-positioned to resume to catch up after the recent deep recession. However, for all neighbour economies the identified weaknesses in their economic structure and governance, and the daunting challenges facing policy makers, not least in the area of fiscal policy, underscore the need to implement far-reaching structural reforms to enhance potential growth and improve resilience."